MENGEMBANGKAN AKTIVITAS, KREATIVITAS, DAN MOTORIK HALUS ANAK KELOMPOK B MENGGUNAKAN PjBL-DI DAN MEDIA BARANG BEKAS - Hafizah, Yeni; Celia Cinantya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low learning activity and creativity of children in pattern-cutting activities. This study aims to analyze the improvement of activity, creativity, and fine motor development through the combination of the Project Based Learning (PjBL) model, Direct Instruction (DI) model, and recycled materials media. This study employs Classroom Action Research (CAR), conducted over four meetings with the stages of planning, action, observation, and reflection. The research setting involved 13 children from Group B at TK Aisyiyah Bustanul Athfal 1 Banjarmasin. Data were collected through observation using observation sheets, and analyzed using both qualitative and quantitative approaches. The results showed improvement by the fourth meeting through the combination of the Project Based Learning and Direct Instruction models along with recycled materials media. Children's activity reached the criterion of "All Children Active" at 100%, children's creativity reached the criterion of "All Children Creative" at 100%, and fine motor development reached the criterion of "Very Well Developed (BSB)" at 100%. Based on these findings, it can be concluded that pattern-cutting activities through the combination of the Project Based Learning model, Direct Instruction model, and recycled materials media successfully improved children's activity, creativity, and fine motor development.